"National Significance": The Evolution and Development of Acquisition Strategies in the Manuscript Division, National Archives of Canada - Momryk, Myron (Archivaria, 2001)
Questions relating to acquisition of private records and "national significance" have been a constant preoccupation in the area of multicultural archives and, more generally, in the area of social and cultural archives. This article describes the evolution of the various attempts to provide answers to these questions in the Manuscript Division of the National Archives of Canada. It looks at some of the pressures to produce generally acceptable solutions from both within and outside the National Archives. In the absence of appropriate solutions, emphasis may shift to process and procedures. The author wrote this article as a participant in these efforts and, also, as an interested observer.